Semantic aspects of the use of real - Cabanchik, Samuel Manuel (1998)
I intend reviewing, in the first place, the contributions to some aspects of the realism issue's discussion coming from some important representatives of the so-called "analytic philosophy". With this in view, I intend to show that Austin's conceptual framework, beyond its elucidating power, excludes main aspects of the aforementioned use. In the second place, starting from some of Moore's contentions, we offer an elucidation of the meaning of the expression ''this is real" in terms of "this may be sought and found". Finally, we project this strategy to clarify the sense and scope of realism's declared independence dimension.